A Simple Approach to Specifying the Weights of the HDI Index - Xiaohua Yu (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
Starting from a representative welfare function, this paper developed a simple method to endogenously specify the weights for the Human Development Index (HDI), and finds that the current equal-weighted HDI significantly biases down the weight of life expectancy. The weights proposed by this study may more properly reflect the humancentered development of the HDI.
Keywords: O15; D6; 330; HDI; Weights; Welfare Function; Ranking